Nous Accusons - Revisiting Foucault's comments on the role of the 'specific intellectual' in the context of increasing processes of Gleichschaltung in Britain - Beckmann, Andrea; Cooper, Charlie (Outlines. Critical Practice Studies, 2005)
In the late nineteenth century, Emile Zola felt the urge and intellectual responsibility to challenge the unethical, unjust and oppressive operation of the French Republic, and wrote an open letter to the President of the Republic entitled ‘J’accuse’. The publication of this open letter led to the formulation of the Manifeste des intellectuals (1897) that demands a non-party space for the expression of an ethically guided politics. ‘J’accuse’ has become a generic symbol for the voicing of resistance against governmental forms of oppression. On the basis of a re-reading of Foucault’s understanding of the ‘specific intellectual’ (Foucault, 1977 and 1980), this article suggests that we need a non-party space for the public expression of ethically governed politics. The article explores some parallels that can be drawn between the historical phenomenon of Gleichschaltung in Nazi Germany and contemporary politics in Britain. While it is aknowledged that the ultimate goals and the ‘legitimating’ ideological frameworks operating in both regimes are very different, various elements of the processes involved in the establishment, maintenance and extension of control over the populace as well as the increasing muting of resistance show remarkable similarities. Paying particular attention to policy and practice in relation to housing, education and “crime control,” contemporary Britain is revealed as characterized by  processes that have so far resulted in opportunistic conformity being the reigning norm of a societal life in which former notions of freedom, civil rights and self-government have become increasingly undermined.